ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI SHARE REPURCHASE (Studi pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2008-2014) - Rahmadhani, Arindra Karunia; Mawardi, Wisnu (Diponegoro Journal of Management, 2016)
This study aims to determine factors that influencing the magnitude of share repurchases. The Independent variables used in this study are dividend payout ratio, market to book ratio, free cash flow, firm size and debt to equity ratio. The population of this study includes all firms registered in Indonesia Stock Exchange that conduct share repurchase program in 2008-2014. Sample choosen using purposive sampling technique with the criteria are share repurchases held by non-financial firms that paying cash dividend in the prior year of repurchase. Approximately 53 repurchases are obtained from 39 sample firms. Multiple Regression Analysis is used to examine the influence of each variable toward share repurchase. The result show that free cash flow have positive and significant effect toward share repurchase. Firm size have positive and significant effect toward share repurchase. Dividend payout ratio have positive but insignificant effect. Market to book ratio have positive but insignificant effect. Debt to equity ratio have negative but insignificant effect toward share repurchase.